Dynamics of Ethnic Politics in Nigeria: An Impediment to its Political System - Adetiba, Toyin Cotties (Journal of Economics and Behavioral Studies, 2019)
Without any form of prejudice, it is a fact that Nigeria is a multi-ethnic state with differences in its socio-political and economic development all of which have resulted in conflicts and counter conflicts. Ethnic politics in Nigeria’s political system have come to be a tragic and constant in Nigeria’s political system; where one must belong to the mainstream of ethnic politics for political relevance. It depicts attachments to the sub-national ethnic groups which threaten to undermine national integration and therefore divide the nation. Significantly, ethnicity in Nigeria was orchestrated by a long period of colonialism, a period which witnessed the ascendancy of the three major ethnic groups in Nigeria to the socio-political domination of other ethnic groups. It was a period when the three major ethnic groups were used by the colonialist as a pedestal for the distribution of socio-political and economic goods. Using a mixed method, this work argues that Nigeria’s political problem hinges on the negative consequences of ethnic politics. The paper concludes that if Nigeria’s political system must progress, it must be anchored on the need for the review of the constitutional and political structure of Nigeria to restore healthy political competition as opposed to the existing outdated political mechanism imposed on Nigeria by the military under the 1999 Constitution of the Federal Republic of Nigeria.